Kenduren Tradition Before Ramadan Fasting: A Phenomenology Study at Umbul Payung Society Central Lampung - Defika Andriana Sari; Muhammad Syaifullah (Journal of Research in Islamic Education, 2021)
various ways that can be done so that humans, especially Muslims, can understand and understand the importance of carrying out one of the third pillars of Islam, namely fasting. Without coercion, it will slowly follow, because everything has become a habit. This article aims to find out about the kenduren tradition in the customs before Ramadan fasting with a phenomenological approach carried out in Umbul Payung village, Bumi Nabung Ilir. This research is phenomenology study where source of primary data from observation, secondary data from studies and relevant information. The findings show that this kenduren tradition is the same as the previous habit. As a reminder that fasting in the month of Ramadan will arrive. In it is inserted some hope in order to get pleasure, smoothness, strength and blessings during the fast. And can return to his holy nature. Thus, the existence of this kenduren tradition is expected to continue, because this is a positive activity and is a way for humans to be closer and always have a peaceful life in their hearts with good intentions in the religion of Allah SWT.